Pengaruh Love of Money dan Machiavellianism Terhadap Kepatuhan Wajib Pajak: Peran Religiusitas - Agung Dwi Nugroho; Amir Hidayatulloh (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2023)
This study aims to analyze the effect of love of money and Machiavellianism on taxpayer compliance with religiosity as a moderating variable. The population of this study is individual taxpayers who carry out independent work in the Special Region of Yogyakarta, while the sample of this study is individual taxpayers who carry out independent work in the Bantul Regency. The sampling technique uses purposive sampling, with the criteria for taxpayers having a Taxpayer Identification Number. Data was collected by distributing questionnaires with the help of Google Forms. The data analysis technique uses Partial Least Square (PLS) with the help of the WarpPLS tool. This study obtained the results that taxpayer compliance was influenced by a love of money, Machiavellianism, and religiosity. However, religiosity does not moderate the effect of love of money and Machiavellianism on taxpayer compliance.